Aerobic but not thermoregulatory gains following a 10‐day moderate‐intensity training protocol are fitness level dependent: A cross‐adaptation perspective. Issue 3 (15th February 2020) - Sotiridis, Alexandros; Debevec, Tadej; Ciuha, Urša; McDonnell, Adam C.; Mlinar, Tinkara; Royal, Joshua T.; Mekjavic, Igor B.
Abstract: Moderate‐intensity exercise sessions are incorporated into heat‐acclimation and hypoxic‐training protocols to improve performance in hot and hypoxic environments, respectively. Consequently, a training effect might contribute to aerobic performance gains, at least in less fit participants. To explore the interaction between fitness level and a training stimulus commonly applied during acclimation protocols, we recruited 10 young males of a higher (more fit‐MF, peak aerobic power [VO2peak ]: 57.9 [6.2] ml·kg −1 ·min −1 ) and 10 of a lower (less fit‐LF, VO2peak : 41.7 [5.0] ml·kg −1 ·min −1 ) fitness level. They underwent 10 daily exercise sessions (60 min@50% peak power output [Wpeak ]) in thermoneutral conditions. The participants performed exercise testing on a cycle ergometer before and after the training period in normoxic (NOR), hypoxic (13.5% Fi O2 ; HYP), and hot (35°C, 50% RH; HE) conditions in a randomized and counterbalanced order. Each test consisted of two stages; a steady‐state exercise (30 min@40% NOR Wpeak to evaluate thermoregulatory function) followed by incremental exercise to exhaustion. VO2peak increased by 9.2 (8.5)% ( p = .024) and 10.2 (15.4)% ( p = .037) only in the LF group in NOR and HE, respectively. Wpeak increases were correlated with baseline values in NOR ( r = −.58, p = .010) and HYP ( r = −.52, p = .018). MF individuals improved gross mechanical efficiency in HYP. Peak sweat rate increased in both groups in HE, whereas MF participants activated the forehead sweating response at lower rectal temperatures post‐training. In conclusion, an increase in VO2peak but not mechanical efficiency seems probable in LF males after a 10‐day moderate‐exercise training protocol. Abstract : Whether a substantial training effect can be potentiated by short‐term acclimation protocols that include exercise sessions remains unresolved. Here, we demonstrate that a training effect might contribute to aerobic gains only in individuals of a lower fitness level that participate in heat‐acclimation protocols.